1988
DOI: 10.1002/food.19880320613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the drying process on the nutritive value of milk Part 2. Biological evaluation

Abstract: Five different brands of dry milk and freeze dried milk were used in rat feeding trials to study their nutritive value and to assess the effect of the drying process on their nutritive value by using growth response, weight gain, food efficiency and relative nutritive value (RNV). Brand I milk gave better growth response, weight gain and food efficiency than any other dry milk studied, while brand V gave the least values. Freeze dried milk gave better growth response, weight gain and food efficiency than brand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…11 The consumption of milk containing oxidized protein has negative effects on children, including lower growth rates, eczema and dry stool. 12,13 In previous studies, we veried that long-term exposure to oxidized casein or oxidized tyrosine impaired the antioxidant defense system and induced hepatic and renal brosis. 14,15 Previous research also suggested that Dityr could induce oxidative damage in the brain, leading to novel object recognition decits.…”
Section: Introductionmentioning
confidence: 99%
“…11 The consumption of milk containing oxidized protein has negative effects on children, including lower growth rates, eczema and dry stool. 12,13 In previous studies, we veried that long-term exposure to oxidized casein or oxidized tyrosine impaired the antioxidant defense system and induced hepatic and renal brosis. 14,15 Previous research also suggested that Dityr could induce oxidative damage in the brain, leading to novel object recognition decits.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, intake of different protein diets during lactation may affect infant growth and development . Previous studies reported the presence of casein oxidation products in spray-dried milk powder, and ingestion of milk powders containing casein oxidation products reduced individual growth responses and caused infant eczema and dry feces. , Fenaille et al. reported different levels of casein oxidation product accumulation in commercially available milk .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Milk powder containing oxidized protein products led to lower growth response and caused eczema and dry stool in infants. 7 Our past research has shown that dietary oxidized casein exposure caused oxidized injury by impairing antioxidant defense system and induced fibrosis injury in mice liver and kidney by accumulating advanced oxidation protein products (AOPPs) and changing the related gene expressions of fibrosis. 8 Several previous studies have also demonstrated that dietary sources of oxidized amino acids may be used for the de novo synthesis of proteins such as enzymes and structural components in cells and potentially contributing to cell malfunction and apoptosis and disease status in body.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently, the increasing interest among food scientists in this field has led one to highlight the influence that consumption of oxidized protein products may have on human nutrition and health. The past decade has showed epidemiological evidence of a positive association between high consumption of red meat or processed meat and the risk of developing a series of diseases, including cardiovascular disease, diabetes, and colorectal cancer. , Milk powder containing oxidized protein products led to lower growth response and caused eczema and dry stool in infants . Our past research has shown that dietary oxidized casein exposure caused oxidized injury by impairing antioxidant defense system and induced fibrosis injury in mice liver and kidney by accumulating advanced oxidation protein products (AOPPs) and changing the related gene expressions of fibrosis .…”
Section: Introductionmentioning
confidence: 99%